2023
DOI: 10.18608/jla.2023.7807
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of MOOCs Revisited? Demographics of Learners Preparing for University

Abstract: This paper leverages cluster analysis to provide insight into how traditionally underrepresented learners engage with entry-level massive open online courses (MOOCs) intended to lower the barrier to university enrolment, produced by a major research university in the United States. From an initial sample of 260,239 learners, we cluster analyze a subset of data from 29,083 participants who submitted an assignment in one of nine entry-level MOOC courses. Manhattan distance and Gower distance measures are compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…MOOCs are closely related to the YouTube education videos we study, and both are purported to provide an avenue of education that is more accessible than traditional universities. However, it is contested whether and to what extent MOOCs do democratize education [25,41,51,76], though work has found that learners who do not have a college degree are more likely to do better on a MOOC than learners with a college degree [63,64]. MOOCs enrollment is often motivated for career building rather than knowledge building [91], and they are typically on a far shorter time scale than a university degree.…”
Section: Background 21 Online Learningmentioning
confidence: 99%
“…MOOCs are closely related to the YouTube education videos we study, and both are purported to provide an avenue of education that is more accessible than traditional universities. However, it is contested whether and to what extent MOOCs do democratize education [25,41,51,76], though work has found that learners who do not have a college degree are more likely to do better on a MOOC than learners with a college degree [63,64]. MOOCs enrollment is often motivated for career building rather than knowledge building [91], and they are typically on a far shorter time scale than a university degree.…”
Section: Background 21 Online Learningmentioning
confidence: 99%
“…The Promise of MOOCs Revisited? Demographics of Learners Preparing for University [28]. From an initial sample of 260,239 learners, we cluster analyze a subset of data from 29,083 participants who submitted an assignment in one of nine entry-level MOOC courses.…”
Section: Literatures Reviewmentioning
confidence: 99%
“…Recent work attempts to fill this gap. Research that examines differences in procrastination behaviour (Sabnis et al, 2022), engagement with LA dashboards , and specific analysis of how demographic subgroups persist in open learning environments (Meaney & Fikes, 2023;Nguyen et al, 2020), have all explicitly collected relevant demographic variables and used them to analyze equity gaps along educational, racial, and socioeconomic lines, among others. More work along these lines is needed.…”
Section: Limited Analysis Of Demographic Subgroupsmentioning
confidence: 99%